J Nanomed Nanotechnol 2019
DOI: 10.35248/2157-7439.19.10.531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Dose of Selenium Nanoparticles on Alimentary Tract in Rodents

Abstract: Nanomedicine & Nanotechnology J o ur nal of N a n o m ed icine & N a n o te chnolo g y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, no significant changes were observed after a 90-day exposure to a dose of 500 mg/kg (Khubulava et al, 2019).…”
Section: Effects Of Np Of Se or Its Compounds On Laboratory Rodents S...mentioning
confidence: 79%
See 3 more Smart Citations
“…However, no significant changes were observed after a 90-day exposure to a dose of 500 mg/kg (Khubulava et al, 2019).…”
Section: Effects Of Np Of Se or Its Compounds On Laboratory Rodents S...mentioning
confidence: 79%
“…Zhang et al (2019) also reported an LD50 of over 36 Se/kg for male and female rats. Lesnichaya et al (2020) found an LD50 of over 2000 mg/kg for mice, while Khubulava et al (2019) reported an LD50 of over 5000 mg/kg for rats.…”
Section: The Median Lethal Dose For the Np Of Se And Its Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Khubulava et al [4] have evaluated the effect of single and continuous high dose of selenium nanoparticles through oral administration on the alimentary tract. The results revealed that multiple exposures at regular intervals was less toxic and did not cause gastritis, gastric metaplasia, haemorrhage or intestinal wall disorganization when compared to single exposure.…”
Section: Editor Notementioning
confidence: 99%